Impacto ambiental de los servicentros en la ciudad de Iquitos en el año 2012 - Cruz Ulloa, Hugo Sigifredo (2015)
The environmental impact generated by the gas stations in Iquitos city was investigated considering their permanent operation and modernization in the last years. The purpose of the investigation was to determine the effects of the environmental impact of the gas stations and to suggest the necessary corrective actions. The material used was the gas stations inventoried. The descriptive research was with no-experimental design, without manipulation of its variables: the products commercialization in the gas stations and the environmental impacts in the soil, water and air, and also the health deterioration. The soil impact was done of gas stations in urban areas, for water from the floating gas stations in the Itaya River and for air was only taken the references of the research done in Trujillo city. The samples were analyzed using specialized equipment for each case, which are installed in the laboratories in the National University of the Peruvian Amazonia. According to surveys, indicators of contamination of soil, water and air reached values of 3,5490, 3,0144 and 3,5598 respectively; similarly, the deterioration health indicator had a value of 3,2387, indicating that in all cases exceed the averages with a favorable trend. From the obtained results it is concluded that the operations of the gas stations in Iquitos city have generated moderate negative impacts contaminating the soil, water and air; and also, it is not a significant danger to deterioration the health of the persons around.